The impact of European integration on the marketing security of domestic business - Bogma, Olena; Silakova, Hanna; Vialets, Oksana (My University, 2022)
У сучасних умовах господарювання забезпечення маркетингової складової економічної безпеки, яка відповідає за затребуваність продукції ринком і можливості провадження успішної ринкової діяльності підприємств, є надзвичайно актуальним, особливо в умовах активізації процесу європейської інтеграції України, яка матиме величезні трансформаційні наслідки як для країни, так і для її бізнесу. Метою статті є систематизація позитивних і негативних наслідків впливу процесу європейської інтеграції на маркетингову складову економічної безпеки бізнесу в Україні як центральної ланки національної економічної системи. У теоретико-методичній площині досліджено трактування маркетингової складової економічної безпеки підприємства з погляду окремих авторів, що дозволило формулювати авторське визначення досліджуваної дефініції. На основі використання системного підходу розглянуто можливості та загрози європейській інтеграції України щодо впливу на маркетингову безпеку вітчизняних підприємств у розрізі основних елементів маркетингової концепції «4Р»: product (товар), price (ціна), place (місце на ринку) та promotional (просування). Розглянуто можливості та загрози європейській інтеграції для маркетингової безпеки вітчизняного бізнесу в розрізі елементу people (люди, споживачі, персонал) та вивчено переваги здійснення ринкової діяльності вітчизняними підприємствами за рахунок реалізації Україною стратегії євроінтеграції. Встановлено необхідність подальшої реалізації Україною проєвропейських реформ для повноцінного використання вітчизняним бізнесом переваг процесу європейської інтеграції. Перспективним напрямком подальших досліджень є вдосконалення використовуваних вітчизняним бізнесом маркетингових стратегій і тактики в умовах функціонування «за європейськими стандартами». In modern conditions of the economic management, ensuring the marketing component of economic security, which is responsible for the demand for products in the market and the possibility of successful market activities of enterprises, is extremely important, especially in the context of activation of the process of the European integration of Ukraine, which will have huge transformational consequences for both the country and its business. The purpose of the article is to systematize the positive and negative consequences of the influence of the European integration process on the marketing component of the economic security of business in Ukraine as the central link of the national economic system. In the theoretical and methodological plane, the interpretation of the marketing component of the economic security of an enterprise from the point of view of individual authors was studied, which made it possible to formulate the authors' own elaboration as to the definition under study. Based on the use of the system approach, the possibilities and threats of the European integration of Ukraine regarding the impact on the marketing security of domestic enterprises in the context of the main elements of the marketing conception “4P” are considered: product, price, place (place in the market), and promotional. The opportunities and threats of European integration for the marketing security of domestic business in the context of the people element (people, consumers, and staff) are considered, and the advantages of market activity by domestic enterprises through the implementation of the European integration strategy by Ukraine are studied. The need for further implementation of pro-European reforms by Ukraine is determined for full-range use of the advantages of the European integration process by domestic business. A promising direction for further research is the improvement of marketing strategies and tactics used by domestic business in the conditions of functioning “up to European standards”.
Keywords: європейська інтеграція; маркетингова безпека підприємства; бізнес; європейський ринок; можливості; European integration; enterprise marketing security; business; European market; opportunities